KETAHANAN API KAYU SENGON (Paraserianthes falcataria (L.) Nielsen) YANG DIAWETKAN DENGAN BAHAN PENGAWET BORAKS: Fire Resistance Of Sengon (Paraserianthes Falcataria (L.) Nielsen) Preserved With Borax (PERENNIAL, 2021)
Wood as building raw materials still very needed, but flammability is one of the detrimental properties. Increasing fire resistance with Borax as fire retardants are needed to increase safety, reduce material and non-material losses due to the impact of fire. The aim of this study was to determine the properties of cold immersion of Sengon in Borax solution for 5 days with different concentrations as a fire retardant. Fire resistance testing used the ASTM E69-02 standard. ANOVA analysis with Completely Randomized Design at the 95% confidence level and LSD (Least Significant Difference) Test. The results showed that immersion Sengon with Borax solution with different concentrations had a significant effect. The average value of the air dry moisture content of the Sengon was 14.08%, the air dry density was 0.33g/cm3, the oven dry density was 0.30g/cm3, the highest Borax preservative retention was at a concentration of 15% of 38.04 kg/m3, the smallest burnst Intensity is 12.58% at 15% concentration, the lowest maximum combustion temperature is 210.1ᵒC at 10% concentration, and the smallest combustion time is 437.5 seconds at 15% concentration. In general, the cold immersion preservation treatment of 15% Borax solution shows the best fire resistance properties, although it still does not meet ASTM E69-02 standards.
Keywords: Borax, Concentration, Cold immersion, Fire Resistance, Retention